The relationship between KLCC Park characteristics and users feeling - Alidi, Ashkan; Ismail, Nor Atiah (Universiti Putra Malaysia Press, 2019)
This study focuses on understanding the effect of the KLCC Park on its visitors' attitudes. Questionnaires were distributed to 90 respondents and their reactions were recorded. In addition, respondent demographics such as gender, ethnic group, occupation, education level and others were also recorded. It was found that an overwhelming majority of the respondents were satisfied with the circulation, safety, recreational, environmental and visual values of the park. Additionally, a majority of participant agreed to a series of statements which suggested that the park impacted their behaviour positively. The respondents were mostly men. Married people outnumbered the other categories, and those within the 30-40 years of age group formed the majority. Most respondents were Muslims who were mainly locals working in the private sector. It was found that the visitors preferred to visit the park in the evening for leisure purposes. A large percentage of them held a tertiary education. The authors conclude that the KLCC Park is a good model to study as it impacts the attitudes of visitors in a positive and healthy manner.